PERBANDINGAN ONSET DAN DURASI BLOK SENSORIK MOTORIK MENGGUNAKAN METODE KOMBINASI BUPIVAKAIN DAN BUPIVAKAIN MURNI PADA PASIEN SEKSIO SESARIA - Utami, Yulia Kartika; Suryani, Shila; Setiawati, Setiawati (Mandala Of Health; Vol 17 No 2 (2024): Mandala of Health: a Scientific Journal, 2024)
Anesthesia plays as an important role in the caesarean section procedure. The use of multimodal analgesia regimen has been considered as the gold standard of anesthesia for patients undergoing cesarean section. This study examines the comparison between the onset and duration of motoric and sensoric nerve blocks in patients undergoing cesarean section with spinal anesthesia using Bupivacaine Combination and Bupivacaine Only at Margono Soekarjo Hospital, Purwokerto. This research was a randomized controlled trial with double blind. Inclusion criteria in this study were patients aged 20-45 years, ASA physical status II and BMI between 18.5-35. Exclusion criteria in this study were patients with anatomical abnormalities or severe congenital abnormalities, contraindications to spinal anesthesia, history of allergy to the anesthetic agents used and unconsciousness patients. Subjects were divided into two groups, each group consists of 15 patients, Bupivacaine Combination (spinal anesthesia with Bupivacaine 7.5 mg + Fentanyl 25 mcg + Morphine 100 mcg) and Bupivacaine Only (spinal anesthesia with Bupivacaine 15 mg). Data were analyzed using Independent Sample T Test with a significance level of α=0.05. There were differences in onset of motoric block (p=0.00), duration of motoric block (p=0.00), onset of sensoric block (p=0.00) and duration of sensoric block (p=0.00) between Bupivacaine Combination and Bupivacaine Only groups. The Bupivacaine Combination group has a slower onset and shorter duration of anesthesia than the Bupivacaine Only group.